Problems in the Implementation of Regional Regulations in Lampung Province as A Result of the Initiative Proposal of the Regional Legislative Council - Pone, Darlian; Ridlwan, Zulkarnain; Firmansyah, Ade Arif (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aims to identify and explain the problems surrounding the implementation of Regional Regulations initiated by the Lampung Provincial House of Representatives (DPRD), particularly in terms of their effectiveness in supporting community welfare. Using a normative legal research method with a statute and theoretical approach, this study analyzed 12 Regional Regulations issued between 2015 and 2023 through content analysis of legal texts and supporting documents. The findings indicate two major issues. First, the absence of follow-up regulations in the form of Governor Regulations creates a legal vacuum, which hinders Regional Apparatus Organizations from operationalizing the Local regulation. Second, there is a fundamental disconnect between the legislative focus of the DPRD which emphasizes accommodating community aspirations and the executive priorities of the Regional Government, which are more programmatic and budget-oriented. As a result, DPRD-initiated Local regulation are often not integrated into regional development planning and remain unimplemented. This study recommends strengthening coordination mechanisms between the DPRD and the Regional Government during the legislative planning stage, as well as mandating a time-bound issuance of implementing regulations to ensure effective enforcement of regional laws.